Biomarker panel predicts survival after resection in pancreatic ductal adenocarcinoma: A multi-institutional cohort study. Issue 2 (February 2019) - Nahm, Christopher B.; Turchini, John; Jamieson, Nigel; Moon, Elizabeth; Sioson, Loretta; Itchins, Malinda; Arena, Jennifer; Colvin, Emily; Howell, Viive M.; Pavlakis, Nick; Clarke, Stephen; Samra, Jaswinder S.; et al.
Abstract: Background: Up to 60% of patients who undergo curative-intent pancreatic ductal adenocarcinoma (PDAC) resection experience disease recurrence within six months. We recently published a systematic review of prognostic immunohistochemical biomarkers in PDAC and shortlisted a panel of those reported with the highest level of evidence, including p53, p16, Ca-125, S100A4, FOXC1, EGFR, mesothelin, CD24 and UPAR. This study aims to discover and validate the prognostic significance of a combinatorial panel of tumor biomarkers in patients with resected PDAC. Methods: Patients who underwent PDAC resection were included from a single institution discovery cohort and a multi-institutional validation cohort. Tumors in the discovery cohort were stained immunohistochemically for all nine shortlisted biomarkers. Biomarkers significantly associated with overall survival (OS) were reevaluated as a combinatorial panel in both discovery and validation cohorts for its prognostic significance. Results: 224 and 191 patients were included in the discovery and validation cohorts, respectively. In both cohorts, S100A4, Ca-125 and mesothelin expression were associated with shorter OS. In both cohorts, the number of these biomarkers expressed was significantly associated with OS (discovery cohort 36.8 vs. 26.4 vs 16.3 vs 12.8 months, P < 0.001; validation cohort 25.2 vs 18.3 vs 13.6 vs 11.9 months, P = 0.008 for expression of zero, one, two and three biomarkers, respectively). On multivariable analysis, expression of at least one of three biomarkers was independently associated with shorter OS. Conclusion: Combinations of S100A4, Ca-125 and mesothelin expression stratify survival after resection of localized PDAC. Co-expression of all three biomarkers is associated with the poorest prognostic outcome.